(untitled) (Plant Tissue Culture and Biotechnology, 2016)
A rapid and an efficient protocol for germination of immature seeds of Vanda tessellata, PLBs development and plant regeneration system have been developed. The results indicate that immature capsules performed better in terms of germination (100.0%) and development of PLBs (90.0%). Around 45 - 60 days old PLBs were transferred to half strength of MS supplemented with different concentrations of auxins and cytokinins. The highest weight of PLBs (5.53 g), the best plant regeneration (16.50) and shoot length (3.25 cm) were recorded when the medium was supplemented with BAP (1.0 mg/l) and NAA (1.5 mg/l). The highest number (5.0) and length (3.22 cm) of roots, the maximum number of plantlets (3.75) were obtained in the medium supplemented with 1.5 mg/l BAP and 1.0 mg/l IAA. The maximum numbers of leaves (3.33) were recorded in the medium fortified with 1.5 mg/l BAP + 1.00 mg/l IAA; the highest length of leaves (2.59 cm) was observed in the medium combining with of BAP and IAA (2.0 mg/l). Well shooted - and rooted plants were acclimated in pots that contained two types of compost. Here, type-II showed better performance on plant development. Plant Tissue Cult. & Biotech. 25(2): 181-191, 2015 (December)